The Application of Wavelet Neural Network in the Settlement Monitoring of Subway - YI Zhenghui; WANG Shuaimin; XU Yujing; LIU Bei (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The settlement monitoring of subway runs through the entire construction stage of subway. It is very important to predict the accurate settlement value for construction safety of subway. In this paper, the wavelet transform is used to denoise the settlement data. The auxiliary wavelet neural network, embedded wavelet neural network and single BP neural network are applied to predict the settlement of Tianjin subway. Compared with single BP neural network and auxiliary wavelet neural network, the embedded wavelet neural network model has a higher accuracy and better prediction effect. The embedded wavelet neural network is more valuable than the BP neural network model so it can be used in the prediction of subway settlement